Evidence of Conjoint Activation of the Anterior Insular and Cingulate Cortices during Effortful Tasks - Engström, Maria; Karlsson, Thomas; Landtblom, Anne-Marie; Craig, A. D. (Bud) (Frontiers in Human Neuroscience, 2015)
The ability to perform effortful tasks is a topic that has received considerable interest in the research of higher functions of the human brain. Neuroimaging studies show that the anterior insular and the anterior cingulate cortices are involved in a multitude of cognitive tasks that require mental effort. In this study we investigated brain responses to effort using cognitive tasks with task difficulty modulations and functional magnetic resonance imaging (fMRI). We hypothesized that effortful performance involves modulation of activation in the anterior insular and the anterior cingulate cortices, and that the modulation correlates with individual performance levels. Healthy participants performed tasks probing verbal working memory capacity using the reading span task, and visual perception speed using the inspection time task. In the fMRI analysis, we focused on identifying effort-related brain activation. The results showed that working memory and inspection time performances were directly related. The bilateral anterior insular and anterior cingulate cortices showed significantly increased activation during each task with common portions that were active across both tasks. We observed increased brain activation in the right anterior insula and the anterior cingulate cortex in participants with low working memory performance. In line with the reported results, we suggest that activation in the anterior insular and cingulate cortices is consistent with the neural efficiency hypothesis (Neubauer).